2008
DOI: 10.1042/bj20071639
|View full text |Cite
|
Sign up to set email alerts
|

Neuropilins: structure, function and role in disease

Abstract: NRPs (neuropilins) are co-receptors for class 3 semaphorins, polypeptides with key roles in axonal guidance, and for members of the VEGF (vascular endothelial growth factor) family of angiogenic cytokines. They lack a defined signalling role, but are thought to mediate functional responses as a result of complex formation with other receptors, such as plexins in the case of semaphorins and VEGF receptors (e.g. VEGFR2). Mutant mouse studies show that NRP1 is essential for neuronal and cardiovascular development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
352
0
7

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 339 publications
(370 citation statements)
references
References 182 publications
(277 reference statements)
11
352
0
7
Order By: Relevance
“…NRP1 overexpression in Panc-1 cells was found to reduce tumor volume and incidence, 31 and there is also evidence pointing to potentially differential or antagonistic roles of NRP1 and NRP2 in tumor cell regulation. 27 In agreement with murine studies, data from human surgical wounds indicate endothelial NRP1 upregulation early in the wound-healing process, that is, by 2 weeks after injury. 26 Thereafter, NRP1 expression is downregulated as tissue repair continues.…”
Section: Differential Neuropilin Expression In Fsgssupporting
confidence: 66%
See 2 more Smart Citations
“…NRP1 overexpression in Panc-1 cells was found to reduce tumor volume and incidence, 31 and there is also evidence pointing to potentially differential or antagonistic roles of NRP1 and NRP2 in tumor cell regulation. 27 In agreement with murine studies, data from human surgical wounds indicate endothelial NRP1 upregulation early in the wound-healing process, that is, by 2 weeks after injury. 26 Thereafter, NRP1 expression is downregulated as tissue repair continues.…”
Section: Differential Neuropilin Expression In Fsgssupporting
confidence: 66%
“…3,25,27 Overexpression of NRP1 has been shown to be positively associated with the metastatic potential, advanced stage, and clinical grade of prostate carcinoma. 28 NRP1 upregulation in gastrointestinal carcinomas seems to correlate with invasive behavior and metastatic potential.…”
Section: Differential Neuropilin Expression In Fsgsmentioning
confidence: 99%
See 1 more Smart Citation
“…73 NP-1 is also expressed by various kinds of human tumor-cell lines and neoplasms. 74 Clinical studies suggest that NP-1 plays a role in tumor growth and disease progression due to mediating VEGF signals. 75,76 Recent studies have shown that semaphorins are secreted from tumor cells as well as macrophages and fibroblasts in the tumor microenvironment, thereby influencing cancers and their microenvironments.…”
Section: Sema7a: a Semaphorin Involved In Inflammatory Responses Via mentioning
confidence: 99%
“…In addition to interaction with plexins, semaphorin signaling can be further modulated by semaphorin co-receptors. Most of the vertebrate-secreted class-3 semaphorins do not directly interact with plexins, but bind to neuropilin co-receptors to activate plexins (Pellet-Many et al, 2008). This interaction is necessary for neural crest migration, since Nrp2 knockout, like the Sema3F knockout, disturbs the segmental neural crest migration pattern (Gammill et al, 2006(Gammill et al, , 2007 and since embryos lacking either Sema3A or Nrp1 show ectopic neural crest cells (Schwarz et al, 2008).…”
Section: Introductionmentioning
confidence: 99%